Belt & Road Initiative – Geopolitical Moves : China’s BRI Signals To India? - Suryanarayana, P. S. (2019)
A positive Chinese gesture towards India on 1 May 2019 reveals Delhi’s relative importance in Beijing’s global foreign policy. While an instantaneous breakthrough in their complex relationship is unlikely, a new trend can be discerned.